Carotenoids acts as reinforcers of the Acholeplasma laidlawii lipid bilayer. - Rottem, S (1979)
Acholeplasma laidlawii cells grown with oleic acid produced much more colored carotenoids than did cells grown with elaidic acid. The amount of carotenoids was decreased 80 to 90% by growing the cells with 0.05 M propionate, resulting in a marked increase in the mobility of both 5-doxylstearate and 12-doxylstearate incorporated into the membranes. The fatty acid composition of the propionate-grown cells differed from that of cells grown without propionate by containing odd-numbered rather than even-numbered saturated fatty acids, but the ratios of saturated to unsaturated fatty acids were the same. To determine whether the carotenoids are the cause for the restricted mobility in the membranes, the carotenoids were selectively removed from A. laidlawii membranes by incubating the membranes with phosphatidylcholine vesicles. The carotenoid-depleted membranes showed an increase in the mobility of the hydrocarbon chains of the spin-labeled fatty acids. Furthermore, the incorporation of carotenoids into artificial membrane vesicles restricted the mobility of the hydrocarbon chain. Our results support the notion that the carotenoids in A. laidlawii act as a rigid insert reinforcing the membrane bilayer.